Realist Strategies of Republican Peace Niebuhr, Morgenthau, and the Politics of Patriotic Dissent - Tjalve, V.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
This book's central claim is that Niebuhr and Morgenthau may be read as heirs to a particularly American republicanism, whose ideal of patriotism as "embedded dissent" is a powerful and much-needed corrective to contemporary vocabularies of international justice, legitimacy, and restraint on both the left and the right.
Keywords: Europe—Politics and government; Political theory; World politics; Political science; European Politics; Political Theory; Political History; Political Science